2020
DOI: 10.1093/heapol/czaa103
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of intimate partner violence during pregnancy in Eldoret, Kenya: exigency for policy action

Abstract: Intimate partner violence (IPV) is sexual, psychological and physical coercive acts used against persons by intimate partners. When IPV occurs during pregnancy (IPVp), it can result in adverse maternal and pregnancy outcomes. No policy nor practice direction exists to address the rates and risk factors of IPVp in Kenya. Determining the prevalence, types and determinants of IPVp in Western Kenya would aid in the identification of pregnant women affected by and/or at risk of IPVp, as well as informing the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 33 publications
(36 reference statements)
7
8
1
Order By: Relevance
“…We revealed that almost one in ten women (9.2%) have experienced violence during pregnancy in Kenya. Although this rate is high, it is lower compared to prevalence rates of 28–67% reported in different health facility based studies in Kenya [ 3 , 20 22 , 24 ]. Clinic-based studies generally show a higher number of women reporting violence vis-à-vis population-based ones [ 3 ].…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…We revealed that almost one in ten women (9.2%) have experienced violence during pregnancy in Kenya. Although this rate is high, it is lower compared to prevalence rates of 28–67% reported in different health facility based studies in Kenya [ 3 , 20 22 , 24 ]. Clinic-based studies generally show a higher number of women reporting violence vis-à-vis population-based ones [ 3 ].…”
Section: Discussioncontrasting
confidence: 55%
“…We ascertained that more than two thirds (67.8%) of pregnant women have experienced emotional violence - which is consistent with previous research findings in health facility based studies in Kenya (55.8%) [ 21 ]. Likewise, we found higher rates of psychological violence than in two Kenyan health facility based studies in Kisumu (29%) and Uasin Gishu County (27.4%) [ 20 , 22 ]. This high rate of emotional violence is alarming, as this form of violence is associated with postnatal depression, anxiety, and other adverse mental health problems [ 6 , 48 ] - which can limit a woman’s ability to care for herself and for her child [ 22 ].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations